GENERAL PB‐ISOTOPE SYSTEMATICS OF SOURCES FOR VOLCANIC ROCKS OF THE LATEST GEODYNAMIC STAGE IN ASIA - S. V. Rasskazov; I. S. Chuvashova; Т. A. Yasnygina; Yi‐min Sun; Е. V. Saranina (Геодинамика и тектонофизика, 2019)
The modern theory of the evolving Earth is based on integrated isotopic data obtained for the accessible part of the planet and cosmic bodies, in which the U–Pb isotope system plays a key role. The theory is tested by the isotope systematics of oceanic basalt sources. The origin of continental volcanic rocks is often interpreted in terms of the isotopic systematics of oceanic basalts. However, such interpretations, as a rule, reveal contradictions arising from differences in the history and current mantle dynamics of oceans and continents. Under the oceans, a mantle material has long lost connection with the accessible Earth tectonic units; under the continents such a connection is often established. The nature of the evolution of deep‐seated processes under the continents remains uncertain and, by analogy with the oceans, requires deciphering in terms of the components of the mantle sources for volcanic rocks. In modern lithospheric plates of the Earth, there are regions ranging in width from hundreds to thousands of kilometers, which are characterized by high strain rates and, consequently, at least one to two orders of magnitude lower viscosity relative to that of the internal stable parts of the plates. This gives them a special structural status of “dispersed plate boundaries”. The isotope‐geochemical studies of volcanic rocks from regions of the unstable Asia revealed the different nature of components in sources, for which particular interpretations have been proposed. In this paper, a general systematics of sources is defined for volcanic rocks of the latest geodynamic stage in Asia through estimating the incubation time on the 207Pb/204Pb versus 206Pb/204Pb diagram. Two domains are designated: (1) low 238U/204Pb (LOMU) derived from the viscous protomantle (VIPMA), and (2) elevated 238U/204Pb (ELMU). The mantle domains evolved from the Earth's primary material between 4.51 and 4.36 Gyr ago, 4.0 and 3.7 Gyr ago, 2.9 and 2.6 Gyr ago, 2.0 and 1.8 Gyr ago, about 0.66 Gyr ago and <0.09 Gyr ago. Melting anomalies of ELMU sources characterize the unstable mantle of Southern Asia, and those of LOMU sources belong to the Japan‐Baikal geodynamic corridor of the transitional region between the unstable mantle of Asia and its stable core. The Late Cenozoic evolution of the Japan‐Baikal geodynamic corridor resulted in cutting the LOMU domain by the Jeju‐Vitim ELMU source line.